TOTAL PHYSICAL RESPONSE METHOD IN FOREIGN LANGUAGE LEARNING - Yunanfathur Rahman (Universitas PGRI Yogyakarta, 2017)
Foreign language is now a must in every level of education. People begin tolisten to foreign language and the try to master it. Listening is the languageskills that are closely related to the daily life of human beings. Listening is theprocess of accepting verbal symbols with caring, understanding, appreciation,and the interpretation of information, here we capture the content ormessages, as well as to understand the meaning of communication. Whilelistening to a foreign language we will hear how the language is spoken.Therefore, listening is a basic skill that must be mastered by learners inlearning a foreign language before speaking, reading and writing skills. But infact, the foreign language learners have difficulties in Listening. The TotalPhysical Response method can desirable overcome this problem.